A new Late Devonian flora from Sonid Zuoqi, Inner Mongolia, northeastern China. (March 2022) - Bai, Lingqi; Huang, Pu; Yang, Ning; Ju, Wenxin; Liu, Jianbo; Basinger, James F.; Xu, Honghe; Xue, Jinzhuang
Abstract: The Silurian and Devonian plant fossil record is the basis for our understanding of the early evolution of land plants, yet our appreciation of early global phytogeographic evolution has been constrained by the focus of most studies on deposits from Europe, North America, and, more recently, South China. Devonian plants have been recorded rarely from northeastern China, and among previous records, few plants have been illustrated and formally described. In this article, megafossil plants representing a Late Devonian-aged (probably Famennian) flora are described from a locality at northern Sonid Zuoqi, Inner Mongolia, NE China. The flora includes Melvillipteris sonidia new species, Archaeopteris sp., and fragments of some other plants. The new plant shows main axes and two orders of lateral branches. The first-order branches of this plant show a typical zigzag appearance and are borne in pairs on main axes. Second-order branches are straight or slightly flexed, and are borne helically or alternately on first-order branches. Sterile ultimate appendages and fertile structures of M . sonidia n. sp. are borne alternately on second-order branches. An associated palynological assemblage, as well as U-Pb ages of detrital zircon grains from adjacent horizons, are also reported, indicating a Late Devonian age in accord with the megafossil plants. The present study contributes to our appreciation of the Devonian floristic diversity of the Xing'an Block, and, through our review of the record of early vascular plants from NE China, more broadly to the understanding of the mid-latitude vegetation of the Northern Hemisphere during the Late Devonian.